The effect of seedbed treatment of seeds by disinfectants and complex water soluble fertilizers on maize productivity - M. V. Petrova; T. R. Toloraya (Зерновое хозяйство России, 2018)
The article deals with the information that treatment of middle early maize hybrid ‘Krasnodarsky 292 AMV’ by disinfectants and complex water soluble fertilizers TMTD, Maxima XL, Semafor and Tabu together with Gidromiks and Lignogumat of potassium improved productivity and Borogum was more efficient with Tabu. The economic analysis showed that the use of TMTD, Maxima XL, Semafor increased the norm of profitability on 17%, 19% and 12% respectively, and the use of Tabu coincided with the control. The seed treatment by the combination of Gidromiks with other variants increased profitability from 27% to 67%, with Lignogumat from 32% to 59%, the combination of Semafor with Borogum gave a significant increase of profitability on 37%, the combination Tabu with Borogum on 42%. The article presents the tree-year study of the effect of maize seed treatment by disinfectants TMTD (4 l/t), Maxima XL (1 l/t), Semafor (2.5 l/t) and Tabu (6 l/t), by the combination with Gidromiks 9200 g/t), Lignogumat (0.5 l/t) and Borogum (1 l/t). The study showed that both separate disinfectants and their combinations do not have a significant effect on the height of maize stem, but increases the area of leaf surface and photosynthetic potential of sowing in comparison with the control untreated seeds. There was an accumulation of dry aboveground weight in the variant with treated seeds, but the productivity of leaf photosynthesis prevailed in the variants with untreated seeds.